Review on Adult Learning Theory and Approach - Vimala, Govindaraju (International Journal Documentation & Research Institute (IJDRI), 2021)
The theory of adult learning and teaching uses skill as a merging perception to relate gaining of knowledge, skills, and attitudes to improved performance. This theory encourages much adult learning as it is a part of constant learning theory that takes place for a lifetime. Adult learning is a lifetime practice whereby knowledge is designed through the transformation of adults' knowledge. The more adult are familiar with this knowledge base, the more effective their training can be, and the more approachable their practice can be to the needs of adult learners. This article presents the theoretical review on adult learning theory and approach in educational perspective.